2008
DOI: 10.1038/nature07246
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in non-verbal number acuity correlate with maths achievement

Abstract: Human mathematical competence emerges from two representational systems. Competence in some domains of mathematics, such as calculus, relies on symbolic representations that are unique to humans who have undergone explicit teaching. More basic numerical intuitions are supported by an evolutionarily ancient approximate number system that is shared by adults, infants and non-human animals-these groups can all represent the approximate number of items in visual or auditory arrays without verbally counting, and us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

84
1,382
9
33

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,316 publications
(1,508 citation statements)
references
References 20 publications
84
1,382
9
33
Order By: Relevance
“…However, it is also possible that the English speakers' differential cultural experience with mathematics and other uses of exact numerosity led to their relatively more precise representation of analog magnitude. Although our current data do not directly speak to this possibility, it is an intriguing avenue for further research (Halberda et al, 2008).…”
Section: Discussionmentioning
confidence: 74%
“…However, it is also possible that the English speakers' differential cultural experience with mathematics and other uses of exact numerosity led to their relatively more precise representation of analog magnitude. Although our current data do not directly speak to this possibility, it is an intriguing avenue for further research (Halberda et al, 2008).…”
Section: Discussionmentioning
confidence: 74%
“…Later on, the influence of parallel surface processing decreases (Rousselle & Noël, 2008) but even adults continue to be sensitive to perceptual dimensions in their numerical judgments (Gebuis & Reynvoet, 2012a, 2012bSzucs, Nobes, Devine, Gabriel, & Gebuis, 2013). Even if the majority of studies currently try to control the influence of perceptual variables when assessing non-symbolic magnitude processing Halberda, Mazzocco, & Feigenson, 2008;Mazzocco, Feigenson, & Halberda, 2011;Piazza et al, 2010;Piazza, Izard, Pinel, Le Bihan, & Dehaene, 2004), the visual stimulus properties (e.g., surface, density) cannot be controlled for in each individual trial (Gebuis & Reynvoet, 2011, 2012a.…”
Section: Discussionmentioning
confidence: 99%
“…Individual differences in mathematics achievement have been related to both symbolic (Durand, Hulme, Larkin, & Snowling, 2005;Holloway & Ansari, 2009) and non-symbolic (Halberda, Mazzocco, & Feigenson, 2008;Mundy & Gilmore, 2009) numerical magnitude comparison tasks and to number line estimation tasks (Booth & Siegler, 2006;Ramani & Siegler, 2008), which are all considered to be reliable indicators of children's understanding of numerical magnitudes (Laski & Siegler, 2007). Most interestingly, Booth and Siegler (2008) demonstrated that children's representations of magnitude, as measured by a number line estimation task, were uniquely predictive of their learning of answers to novel addition problems and of the errors on them.…”
Section: Understanding Numerical Magnitudes and Mathematics Developmentmentioning
confidence: 99%